Band tuning and channel reconfiguration of sound waves in coding topological metamaterials. (15th December 2021) - Song, Xinpei; Chen, Tianning; Cui, Zhanyou; Chen, Chen; Fu, Junjie; Mao, Feiran
Abstract: The adjustment of the working band of the acoustic metamaterials poses a great challenge, limiting their practical applications. Here, a 2-bit coding acoustic valley Hall topological insulator is reported based on the triangle-lattice scatterers. The former and latter bits are employed to control two diverse scatterers and channels, respectively. The gapless band and transmission channel of the topological edge mode can be adjusted under the control of the four different coding sequences and two other cases. In theory, we reveal the topological phase transition, illustrate the topological edge mode, and predict the working bands of the designed valley Hall topological insulator. Both the simulated sound pressure field patterns and experimented transmission spectra agree well with the predicted results, indicating the properties of band tuning and channel reconfiguration of the valley Hall topological insulator. Our design opens up new avenues for designing coding acoustic metamaterials, showing potential in the achievement of the intelligent, flexible, and programmable sound devices.